Influência dos elementos de envoltória no desempenho termo-energético de edifícios institucionais no clima tropical semiárido - Oliveira, Paolo Américo de (Universidade Federal Rural do Semi-Árido, 2017)
Energy efficiency in buildings is related to the accommodation of the building to the local climate. Studies on the bioclimatic architecture and energy efficiency of buildings in the Brazilian semiarid tropical climate are still rare. With an implementation of instruments establishing differentiated architectural recommendations, according to the climatic situation, the planning and building more suitable for optimal use of electricity buildings is necessary. This study analyzes the influence of the architectural variables in the electricity consumption of institutional buildings located on the campus UFERSA, Mossoró/RN, whose climate is tropical semi-arid. For this, data were collected through architectural projects and surveys in the buildings. Information registered were related to: morphological characterization of buildings, identification of characteristics such as number of floors, arrangement and use of environments, cardinal orientation of facades, arrangement of transparent elements such as windows and doors and the thermal properties of the materials in constructive systems used. For the evaluation of thermal and energetic performance of the identified parameters was used EnergyPlus, that estimates the electricity consumption of land throughout the year using similar models simulating the target buildings in this study. From this procedure, it was found that the architectural variables directly influence the energy consumption of buildings and a list of recommendations was proposed to be followed so that the future constructions of buildings in semiarid tropical climate be more thermal and energetic efficient
Influence of envelope elements in the thermal-energetic performance of institutional buildings in tropical semi-arid climate
Keywords: Arquitetura bioclimática; Eficiência energética; Simulação computacional; Bioclimatic architecture; Energy efficiency; Computational simulation; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE